2015
DOI: 10.1007/s11914-015-0274-z
|View full text |Cite
|
Sign up to set email alerts
|

Fall and Fracture Risk in Sarcopenia and Dynapenia With and Without Obesity: the Role of Lifestyle Interventions

Abstract: Due to their differing etiologies and consequences, it has been proposed that the term "sarcopenia" should revert to its original definition of age-related muscle mass declines, with a separate term, "dynapenia", describing muscle strength and function declines. There is increasing interest in the interactions of sarcopenia and dynapenia with obesity. Despite an apparent protective effect of obesity on fracture, increased adiposity may compromise bone health, and the presence of sarcopenia and/or dynapenia ("s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
0
15

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(77 citation statements)
references
References 116 publications
1
61
0
15
Order By: Relevance
“…Loss of muscle mass due to sarcopenia also affects dynapenia. Several studies indicated that older adults with dynapenia have increased risk of functional disability [87], falling [70] and metabolic diseases [88], even after adjusting for sarcopenia [89]. In our earlier study, we found that individuals with lower muscle strength (the lowest 20th percentile) compared with the moderate or high muscle strength (upper 80th percentile) had over two-fold higher risk of developing metabolic syndrome in both young (<50 years) and old (≥50 years) men after adjusting for age, smoking and alcohol intake [90].…”
Section: Discussion (Current Limitations and Future Direction)mentioning
confidence: 99%
See 1 more Smart Citation
“…Loss of muscle mass due to sarcopenia also affects dynapenia. Several studies indicated that older adults with dynapenia have increased risk of functional disability [87], falling [70] and metabolic diseases [88], even after adjusting for sarcopenia [89]. In our earlier study, we found that individuals with lower muscle strength (the lowest 20th percentile) compared with the moderate or high muscle strength (upper 80th percentile) had over two-fold higher risk of developing metabolic syndrome in both young (<50 years) and old (≥50 years) men after adjusting for age, smoking and alcohol intake [90].…”
Section: Discussion (Current Limitations and Future Direction)mentioning
confidence: 99%
“…SO is associated with or leads to several adverse outcomes with increased risks of mobility disability [4–6], falling and fracture [70], low quality of life and independence [49], metabolic diseases [7,8] and cardiovascular diseases [9–11], which increases risk of premature mortality [12–14]. Potential mechanisms for the development of SO and its health problems include increased insulin resistance [20,56], increased chronic inflammation [58,71], decreased hormones (testosterone, growth hormone, DHEA, IFG-1) [72], decreased neuromuscular function [73–75] and decreases in energy expenditure and fat oxidation [76].…”
Section: Mechanisms Linking Physical Activity To Sarcopenic Obesitymentioning
confidence: 99%
“…Moreover, this definition is likely limited in its ability to predict risk, as consensus population measures of obesity in men, such as BMI (≥ 30 kg/m 2 [99] ) and total body percent fat mass (> 30% [100] ), were not utilised. Of these two measures, a total body percent fat mass > 30% has been commonly suggested as a more appropriate indicator of obesity when compared to BMI [101] ; thus, this cut-off should be utilised when available.…”
Section: Sarcopenic Obesitymentioning
confidence: 99%
“…Obesity was defined as BMI ≥ 30 kg/m 2 [99] or total body percent fat mass ≥ 30% [100] , with the latter commonly deemed a more appropriate indicator of obesity when compared to BMI [101] . There are no consensus definitions for sarcopenic obesity, thus sarcopenic obesity was defined as concurrent sarcopenia (EWGSOP) and obesity (total body percent fat mass ≥ 30%) and pre-sarcopenic obesity was defined as concurrent pre-sarcopenia (ALMI ≤ 7.26 kg/m 2 or ALMI ≤ 7.49 kg/m 2 ) and obesity (total body percent fat mass ≥ 30%).…”
Section: Pre-sarcopenia Sarcopenia Obesity and Sarcopenic Obesitymentioning
confidence: 99%
“…Greater soft-tissue thickness over the lateral hip dissipates fall impact, and so may continue to protect against hip fracture at high body weight even when load-to-strength ratio is exceeded [12,14]. Intramuscular fat content is increased in obesity, and may be associated with poorer muscle function and increased fracture risk ('dynapenic obesity') [15,16]. Poorer muscle function could increase falls and injury when falling, and there are data showing an excess of falls in obese people [17].…”
Section: Obesity Fracture and Bmdmentioning
confidence: 99%